A nanocatalytic drug and its preparation method and application

By constructing heterojunctions of carbon nitride nanosheets and copper-coordinated metal-phase molybdenum disulfide nanosheets in nanocatalytic drugs and performing targeted modifications, a multifunctional nanocatalytic drug T-HCN@CuMS was prepared, which solved the problem of insufficient efficacy of existing nanocatalytic drugs, and achieved efficient treatment of osteosarcoma and inhibition of lung metastasis.

CN117427184BActive Publication Date: 2025-03-21ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311285078.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-03-21
Estimated Expiration
2043-10-07

AI Technical Summary

Technical Problem

In actual application of existing nanocatalytic drugs, due to insufficient tissue penetration ability of external light stimulation, mismatch of the optimal conditions of the tumor microenvironment and Fenton/Fenton-like reaction, and poor tumor targeting of nanocatalytic drugs, the therapeutic effect is insufficient.

Method used

By designing a heterojunction based on carbon nitride nanosheets and copper-coordinated metal-phase molybdenum disulfide nanosheets, T-HCN@CuMS, a bone tumor-targeted multifunctional nanocatalytic drug. The drug has the functions of near-infrared photocatalytic therapy, chemocatalytic therapy and inducing cellular copper death.

Benefits of technology

This nanocatalytic drug responds to near-infrared light through the antenna effect of CuMS, catalyzes the production of reactive oxygen species, and releases catalytic Fenton-like reactions through the responsiveness of copper ions, significantly improving the killing efficacy of osteosarcoma cells, effectively inhibiting lung metastasis, and improving the safety and effectiveness of treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117427184B_ABST
    Figure CN117427184B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a nanocatalytic drug, comprising: (1) dispersing metal phase molybdenum disulfide 1T-MoS2 nanosheets, adding a copper chloride solution, and reacting to obtain copper coordinated metal phase molybdenum disulfide nanosheets CuMS; (2) dispersing carbon nitride HCN nanosheets, adding CuMS, and reacting to obtain a nanocatalytic drug HCN@CuMS; (3) dispersing the nanocatalytic drug HCN@CuMS, and adding cRGD fk PEG 2k ‑DSPE, and obtain a nanocatalytic drug T‑HCN@CuMS with bone tumor targeting. The present invention also provides a nanocatalytic drug obtained by the above preparation method and its application in the preparation of bone tumor drugs. The nanocatalytic drug prepared by the present invention has the functions of near-infrared photocatalytic therapy, chemical catalytic therapy, and inducing cell copper death, and can be used in the preparation of bone tumor drugs to achieve efficient treatment of in situ osteosarcoma.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bone tumors, and particularly relates to a nano-catalytic drug and a preparation method and application thereof. Background Art

[0002] Osteosarcoma in situ is the most common malignant bone tumor. Most cases occur in children and young people aged 10 to 30 years old. The peak incidence is during puberty. The most common sites are the knee joint (distal femur and proximal tibia) and shoulder (proximal humerus). Clinically, a comprehensive treatment model of surgery combined with postoperative radiotherapy and chemotherapy is usually used. Although the 5-year survival rate of patients with local osteosarcoma has increased to about 60%, the survival rate of patients with metastatic and recurrent osteosarcoma is only 20%. Designing and preparing new nanomedicines for safe and efficient treatment of osteosarcoma and effective inhibition of tumor metastasis and recurrence is a key technical problem in the development of bone tumor nanomedicines.

[0003] Nanocatalytic therapy refers to the use of nanocatalytic drugs, or the use of oxygen molecules and water molecules under near-infrared (NIR), ultraviolet-visible (UV-vis) and X-ray radiation to catalyze the production of highly oxidative reactive oxygen species (ROS) such as singlet oxygen, hydroxyl free radicals and superoxide anions, or the use of characteristic biochemical conditions produced by the different metabolic pathways of tumor cells and normal cells, such as slightly acidic environment and endogenously overexpressed hydrogen peroxide (H2O2, 0.1-1mM), to catalyze the Fenton / Fenton-like reaction to produce cytotoxic hydroxyl free radicals, or catalyze the production of a variety of reactive oxygen species under ultrasonic stimulation, causing damage to tumor cells and inducing tumor cell apoptosis. Because tumor cells have a lower oxidative stress threshold, they are more susceptible to reactive oxygen-mediated damage, and reactive oxygen species have a short life span and will not accumulate in large quantities in the body. The occurrence of catalytic reactions is constrained by external stimuli and tissue microenvironment, and catalytic therapy can also be limited to specific sites, which minimizes damage to normal tissues and becomes a very ideal new method for the treatment of malignant bone tumors. For example, a nanocatalyst for tumor treatment disclosed in the Chinese patent with publication number CN110974978A includes a red blood cell membrane and a composite nanozyme and a photosensitizer coated in the red blood cell membrane; the composite nanozyme includes glucose oxidase and iron nanoparticles wrapped in the inner cavity of the glucose oxidase. And a Chinese patent with publication number CN113786486A discloses a homologous targeted tannic acid copper albumin composite nanoparticle and its preparation method and anti-tumor application: the targeted tannic acid copper albumin composite nanoparticle includes a nanoparticle core, a tannic acid and copper complex coated outside the nanoparticle core, and a cancer cell membrane with targeting ability, and the nanoparticle core is composed of albumin and glucose oxidase adsorbed on the albumin.

[0004] However, in actual applications, factors such as insufficient tissue penetration of external light stimulation, mismatch between the tumor microenvironment and the optimal conditions of Fenton / Fenton-like reactions (pH 3-4), and poor tumor targeting of nanomedicines have greatly reduced the efficacy of nanocatalytic drugs.

[0005] Therefore, developing a targeted multifunctional nanocatalytic drug with excellent performance through rational design and material preparation is of great significance for nanocatalytic therapy. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a nanocatalytic drug. The prepared nanocatalytic drug has the functions of near-infrared photocatalytic therapy, chemical catalytic therapy, and inducing cell copper death, and can be used in the preparation of bone tumor drugs to achieve efficient treatment of in situ osteosarcoma.

[0007] The present invention provides the following technical solutions:

[0008] A method for preparing a nanocatalytic drug, the preparation method comprising:

[0009] (1) After dispersing metal phase molybdenum disulfide 1T-MoS2 nanosheets, adding copper chloride solution to react to obtain copper coordinated metal phase molybdenum disulfide nanosheets CuMS;

[0010] (2) dispersing carbon nitride HCN nanosheets and adding CuMS to obtain nanocatalytic drug HCN@CuMS;

[0011] (3) Disperse the nanocatalytic drug HCN@CuMS and add cRGD fk -PEG 2k -DSPE, and obtained the bone tumor-targeting nanocatalytic drug T-HCN@CuMS.

[0012] The present invention uses carbon nitride nanosheets (HCN) as the base material, uses copper coordinated metal phase molybdenum disulfide nanosheets (CuMS) and carbon nitride nanosheets to construct a heterojunction, and through surface targeted modification (cRGD fk -PEG 2k -DSPE), a bone tumor-targeted multifunctional nanocatalytic drug T-HCN@CuMS was prepared.

[0013] In step (1), the preparation method of the 1T-MoS2 nanosheets is: dissolving ammonium heptamolybdate tetrahydrate and thiourea together and then performing a hydrothermal reaction to obtain a metallic phase molybdenum disulfide material 1T-MoS2; ultrasonically exfoliating the 1T-MoS2, and obtaining 1T-MoS2 nanosheets in the range of 9000-12000rpm by step-by-step centrifugation.

[0014] The molar mass ratio of the tetrahydrated ammonium heptamolybdate and thiourea is 1:1-30, the temperature of the hydrothermal reaction is 180-200° C., and the reaction time is 18-24 hours.

[0015] The feeding ratio of the 1T-MoS2 nanosheets to the copper chloride is: 1 to 5 mL of 8 mM copper chloride solution is added for every 10 mg of 1T-MoS2 nanosheets. After adding the copper chloride solution, sufficient ultrasonic stirring is performed to allow the copper ions to be fully coordinated and bonded to the surface of the 1T-MoS2 nanosheets.

[0016] In step (1), after the copper ions are coordinated and modified on the surface of the metal phase molybdenum disulfide nanosheets, the divalent copper ions are reduced in situ and exist mainly in a monovalent form, which greatly improves the utilization rate of copper ions in catalyzing Fenton-like reactions and inducing cell copper death.

[0017] In step (2), the preparation method of the HCN nanosheets is:

[0018] (2-1) calcining urea in an air atmosphere to obtain a bulk carbon nitride material;

[0019] (2-2) mixing a mixture of sodium chloride and potassium chloride with a bulk carbon nitride material and calcining the mixture in a nitrogen atmosphere to obtain carbon nitride powder;

[0020] (2-3) adding carbon nitride powder into a nitric acid solution to obtain acidified carbon nitride;

[0021] (2-4) The acidified carbon nitride is ultrasonically exfoliated in an aqueous solution, and HCN nanosheets in the range of 8000-10000 rpm are obtained by stepwise centrifugation.

[0022] In step (3), the added amount of CuMS is 5-20% of the HCN nanosheets.

[0023] The present invention also provides a nanocatalytic drug obtained according to the above preparation method.

[0024] The present invention also provides an application of the nano-catalytic drug in preparing bone tumor drugs.

[0025] The bone tumor is a malignant bone tumor.

[0026] The technical principle of the above application is that the nanocatalytic drug T-HCN@CuMS provided by the present invention, through the antenna effect of CuMS, gives T-HCN@CuMS the property of responding to near-infrared light, using water molecules and oxygen molecules to catalyze the production of a large number of active oxygen species such as singlet oxygen, hydroxyl radicals and superoxide anions. The copper ions in T-HCN@CuMS are released responsively through the tumor microenvironment, catalyzing the Fenton-like reaction to produce hydroxyl radicals, and inducing copper death in tumor cells. Through the combination of near-infrared photocatalysis-chemical catalysis-copper death and surface targeted modification, the shortcomings of insufficient efficacy of nanocatalytic drugs in actual applications caused by factors such as insufficient tissue penetration of external light stimulation, mismatch between the tumor microenvironment and the optimal conditions of Fenton / Fenton-like reactions, and low tumor targeting of nanocatalytic drugs are overcome.

[0027] Compared with the prior art, the present invention has the following excellent effects:

[0028] The preparation method provided by the present invention prepares a tumor-targeted multifunctional nanomedicine that has near-infrared photocatalytic therapy, chemical catalytic therapy, and induction of cell copper death through phase regulation, ion coordination, heterogeneous structure construction, and targeted modification. It can produce reactive oxygen and induce tumor cell copper death through a large amount of catalysis, thereby being used for the efficient treatment of in situ osteosarcoma and achieving significant inhibition of in situ bone tumor lung metastasis. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the preparation and application of the multifunctional nanocatalytic drug T-HCN@CuMS targeting bone tumors.

[0030] Figure 2 Actual pictures and transmission electron microscope characterization pictures of HCN@CuMS with different proportions.

[0031] Figure 3 X-ray photoelectron spectroscopy (XPS) characterization of CuMS.

[0032] Figure 4 These are the characterization results of HCN@CuMS using atomic force microscopy (AFM), X-ray diffraction (XRD), Richter transform infrared spectroscopy (FT-IR), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS).

[0033] Figure 5 UV-visible-near infrared absorption spectra of HCN@CuMS, electrochemical impedance spectroscopy (EIS), 808 nm laser irradiation (0.15 W cm -2 ) Transient photocurrent response, electron spin resonance spectroscopy measurement under 808nm laser irradiation (0.15W cm -2 ) The properties of the catalytic generation of active oxygen and the types of active oxygen generated.

[0034] Figure 6 Investigation of the properties of HCN@CuMS.

[0035] Figure 7 The tumor cell phagocytosis amount of HCN@CuMS before and after targeted modification and the subcellular localization within tumor cells.

[0036] Figure 8 Different concentrations of T-HCN@CuMS at 808 nm, 0.15 W cm -2 Killing performance of bone tumor cells U2OS and 143B under light stimulation.

[0037] Fig. 9 To investigate the bone tumor cell-killing properties of bone tumor targeted nanocatalytic drug T-HCN@CuMS in vitro.

[0038] Fig.10 The properties of T-HCN@CuMS inducing copper death of tumor cells.

[0039] Fig.11 The effect of T-HCN@CuMS on the migration and invasion ability of bone tumor 143B cells.

[0040] Fig.12 Blood compatibility test of T-HCN@CuMS.

[0041] Fig.13 Verification of the performance of T-HCN@CuMS in treating orthotopic bone tumors in nude mice in vivo.

[0042] Fig.14 The distribution of tumor-targeted and non-targeted modified HCN@CuMS in tumor-bearing nude mice after tail vein injection.

[0043] Fig.15 The solid images, tumor volume change curves, and weight change curves of tumor-bearing nude mice in different treatment groups after treatment.

[0044] Fig.16 Solid images and fluorescent images of representative lung tissues in different treatment groups.

[0045] Fig.17 H&E staining of tumor tissues in different treatment groups, TUNEL apoptosis staining, immunohistochemical staining of tumor cell proliferation marker Ki67, immunofluorescence staining of copper death markers DLAT, FDX1, and LIAS, and immunofluorescence staining of tumor migration marker ESM1, as well as statistical analysis of Ki67, FDX1, LIAS, and ESM1.

[0046] Fig.18H&E staining of the main tissues and organs of nude mice, including heart, liver, spleen, lung, and kidney, in different treatment groups.

[0047] Fig.19 Blood routine and biochemical indexes of liver and kidney function were measured in nude mice in different treatment groups. DETAILED DESCRIPTION

[0048] In order to better understand the technical solution of the present application, the following examples are used to describe the implementation of the invention. It should be clear that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0049] Preparation and application of the bone tumor targeted multifunctional nanocatalytic drug T-HCN@CuMS provided by the present invention Figure 1 shown.

[0050] Example 1

[0051] The preparation method of the nanocatalytic drug T-HCN@CuMS provided in this embodiment includes:

[0052] 10 g of urea was calcined at 500° C. in an air atmosphere for 2 h and then cooled to room temperature to obtain a bulk carbon nitride material.

[0053] Then, a mixture of sodium chloride and potassium chloride (6 g, sodium chloride / potassium chloride, 76 / 24 mol%) and the above calcined product were thoroughly ground and mixed, and the mixture was calcined at 550°C in a nitrogen atmosphere (flow rate 5 L / min) for 2 h. The product was washed with ultrapure water and dried to obtain carbon nitride powder.

[0054] 1 g of the above carbon nitride powder was weighed and added into 100 mL of nitric acid solution (5 M), refluxed in an oil bath at 130° C. for 24 h, washed with water until neutral, and then redispersed in water to obtain acidified carbon nitride.

[0055] The acidified carbon nitride is subjected to ultrasonic exfoliation in an aqueous solution, and carbon nitride nanosheets (HCN) in the range of 8000-10000 rpm are obtained by step-by-step centrifugation for use.

[0056] Dissolve 1.236g of ammonium heptamolybdate tetrahydrate and 2.284g of thiourea in 35mL of water, stir evenly and transfer to a hydrothermal reactor, perform hydrothermal reaction at 200℃ for 24h, cool naturally to room temperature, wash with pure water after centrifugation, and obtain metallic phase molybdenum disulfide (1T-MoS2) material.

[0057] The 1T-MoS2 was ultrasonically exfoliated, and the 1T-MoS2 nanosheet solution in the range of 9000-12000 rpm was obtained by step-by-step centrifugation for use.

[0058] Disperse 10 mg of the above 1T-MoS2 nanosheets in water, add copper chloride solution (8 mM, 1 mL), disperse evenly by ultrasonication and stir at room temperature overnight. The product is copper-coordinated metal phase molybdenum disulfide nanosheets (CuMS), which are centrifuged and washed with water for later use.

[0059] 10 mg of carbon nitride nanosheets were evenly dispersed in water, and CuMS equivalent to 0-20% of the mass of the carbon nitride nanosheets was added (0%, 5%, 10%, 15% and 20% were added respectively, and 0% was used as a control group), stirred at room temperature overnight, centrifuged and resuspended in water to obtain the nanocatalytic drug HCN@CuMS.

[0060] The above nanocatalytic drug HCN@CuMS was evenly dispersed in 10 mL of water and 20 mg of cRGD was added. fk -PEG 2k -DSPE, stirred at 4°C overnight, centrifuged and resuspended in water to obtain the bone tumor-targeting nanocatalytic drug T-HCN@CuMS.

[0061] like Figure 2 Shown are the physical pictures and transmission electron microscope characterization pictures of HCN@CuMS with different proportions.

[0062] Figure 3 X-ray photoelectron spectroscopy (XPS) characterization of CuMS. (A) Total element spectrum, (B) XPS characterization of Cu element, (C) Auger spectrum of Cu element.

[0063] Figure 4 Characterization of HCN@CuMS: (A) atomic force microscopy (AFM), (B) X-ray diffraction (XRD), (C) Fourier transform infrared spectroscopy (FT-IR), (D) Raman spectroscopy, and (EG) X-ray photoelectron spectroscopy (XPS) characterization results.

[0064] Figure 5 (A) UV-Vis-NIR absorption spectra of HCN@CuMS, (B) electrochemical impedance spectroscopy (EIS), and (C) 808 nm laser irradiation (0.15 W cm -2 ) Transient photocurrent response, (D) Electron spin resonance spectroscopy measurement under 808 nm laser irradiation (0.15 W cm -2 ) The properties of the catalytic generation of active oxygen and the types of active oxygen generated.

[0065] Performance Testing:

[0066] HCN@CuMS and T-HCN@CuMS were dispersed in water, 1×PBS solution, FBS, and DMEM culture medium to observe the dispersibility of nanocatalytic drugs in different solutions before and after surface modification. The results are shown in Figure 2. Figure 6 As shown in A.

[0067] The Zeta potential of HCN, CuMS, HCN@CuMS and T-HCN@CuM was tested. Figure 6 As shown in B.

[0068] Preparation of T-HCN@CuMS aqueous solution (1.0 mg mL -1 ). PBS with different pH values ​​(7.4 and 5.0) was mixed with T-HCN@CuMS solution at a volume ratio of 1:1. The mixture was incubated in a shaker at 37°C. 1 mL of the solution was centrifuged at different time points (0, 1, 2, 4, 6, 12, 24 h), and the copper concentration in the supernatant was determined by ICP-MS. The responsive release of copper ions in T-HCN@CuMS was calculated, and the results are shown in Figure 6 As shown in C.

[0069] Preparation of T-HCN@CuMS aqueous solution (1.0 mg mL -1 The material solution was observed by infrared thermal imaging under 808nm laser (0.15W cm -2 ) The temperature changes after irradiation for different time periods were used to evaluate the photothermal conversion effect of the nanocatalytic drug. PBS solution was used as the control group. The results are shown in Figure 6 As shown in F.

[0070] To study the endocytosis of tumor cells to different functionalized HCN@CuMS nanocatalytic drugs, 143B cells were first cultured at 1×10 5 / dish were inoculated in the confocal dish and cultured at 37℃ for 24h. HCN@CuMS and T-HCN@CuMS nanocatalytic drugs (green) were labeled with FITC and co-cultured with 143B cells for 12h, washed with PBS three times, and then the cell nuclei were stained with Hoechst 33258 (blue). The endocytosis of HCN@CuMS and T-HCN@CuMS by tumor cells was observed under a confocal microscope. The tumor cell phagocytosis amount of HCN@CuMS before and after targeted modification and the subcellular localization in tumor cells were shown in Figure 2. Figure 7 shown.

[0071] Transwell assay was used to analyze the effect of T-HCN@CuMS on the migration and invasion of tumor cells. 5Each 143B cell was suspended in 150.0 μL serum-free culture medium, inoculated in the upper chamber, and cultured in 500.0 μL DMEM culture medium containing 10% fetal bovine serum (FBS). After different interventions, 4% polyformaldehyde was added to fix the cells and stained with 0.4% crystal violet. The stained cells were photographed under an inverted microscope and counted using ImageJ software. In the invasion experiment, the chamber was pre-coated with diluted Matrigel (dilution ratio 1:8, 356234, BD, USA), and the rest of the steps were consistent with the migration experiment. The results of the effect of T-HCN@CuMS on the migration and invasion ability of bone tumor 143B cells are shown in Figure 2. Fig.11 shown.

[0072] Take 1.0 mL of BALB / c nude mouse blood and centrifuge at 2000 rpm for 10 min to separate red blood cells. Dilute the red blood cells to 10.0 mL with PBS, and mix 0.2 mL of red blood cell solution with 0.8 mL of deionized water, PBS, or a concentration of 25.0-800.0 μg mL -1 The T-HCN@CuMS suspension was mixed, vortexed and stored at room temperature for 4 h. The mixture was then centrifuged to observe whether hemolysis occurred. The blood compatibility test results of T-HCN@CuMS are shown in Fig.12 shown.

[0073] The nude mouse orthotopic osteosarcoma model was established using luciferase-labeled 143B cells. Six groups were set up, including PBS, PBS+L, T-HCN@MS, T-HCN@MS+L, T-HCN@CuMS, and T-HCN@CuMS+L, with 10 mice in each group. The dosage of nanodrug was 10 mg kg -1 The laser irradiation conditions for the phototherapy group were 808 nm, 0.15 W cm -2 . On the 0th, 10th and 20th days of treatment, the in situ tumor tissue of tumor-bearing nude mice was imaged with a small animal optical imager to observe the size of the tumor tissue and measure the fluorescence intensity, and the fluorescence intensity was compared and analyzed. After 20 days of treatment, the tumor tissue was separated, and the size and weight of the tumor tissue were measured and analyzed. After the treatment, the tumor-bearing nude mice were kept for 50 days to observe their survival. Among them, the performance verification results of T-HCN@CuMS in vivo treatment of nude mice with in situ bone tumors are as follows Fig.13 As shown in Figure 2, the distribution of tumor-targeted and non-targeted modified HCN@CuMS in tumor-bearing nude mice after tail vein injection is shown in Figure 2. Fig.14 shown.

[0074] Application Example 1

[0075] Experimental study on the degradation of methylene blue by producing hydroxyl radicals catalyzed by HCN@CuMS in vitro Fenton-like reaction.

[0076] Prepare 10 μg mL -1 of methylene blue, 10 mM H2O2, and 200 μg mL -1 The mixed solution of HCN@CuMS was prepared by using the principle that hydroxyl radicals produced by monovalent copper ions oxidize the discoloration of methylene blue. The absorbance of the solution at 650nm was measured at different time points to calculate the oxidation percentage of methylene blue. CuMS and HCN@MS were used as control experimental groups. Figure 6 As shown in D.

[0077] Application Example 2

[0078] Experimental study on the degradation of rhodamine B by catalyzing the production of reactive oxygen species in response to 808 nm light in vitro.

[0079] 20 mg of T-HCN@CuMS was mixed with 50 mL of rhodamine B (RhB, 10 μg mL -1 ) were mixed and stirred evenly in the dark. The laser irradiation conditions were 808 nm, 0.15 W cm -2 The absorbance of the solution was measured every 30 minutes, and the degradation rate of RhB was calculated. The experimental results are shown in Figure 6 As shown in E.

[0080] Application Example 3

[0081] T-HCN@CuMS kills bone tumor cells through a cell experiment using the combined effects of near-infrared photocatalysis, chemical catalysis, and induced copper death.

[0082] 143B cells were seeded in a 96-well plate and cultured overnight at 37°C. 150 μg mL -1 After incubation of T-HCN@CuMS nanomedicine for 4-6 h, the -2 Laser irradiation treatment for 10 minutes. CCK-8 detection kit, Live / Dead staining kit, intracellular reactive oxygen species detection kit, mitochondrial membrane potential detection kit, Anexin-V-FITC / PI apoptosis detection kit were used to detect the survival of tumor cells, the amount of intracellular reactive oxygen species produced, and the changes in mitochondrial membrane potential and cell membrane phosphatidylserine externalization and other apoptotic phenotypes. Immunofluorescence was used to analyze the aggregation of intracellular copper death marker protein DLAT. The results are shown in Figure 8-Figure 10 shown.

[0083] Different concentrations of T-HCN@CuMS at 808 nm, 0.15 W cm -2 The performance of killing bone tumor cells U2OS and 143B under light stimulation is as follows Figure 8As shown in the figure, the targeted nanocatalytic drug T-HCN@CuMS showed better killing performance against two osteosarcoma cell lines (143B and U2OS) under near-infrared light conditions, showing significantly enhanced anti-tumor efficiency. This shows that surface targeted modification can significantly improve the efficacy of nanomedicines.

[0084] In vitro investigation of the killing properties of bone tumor cells by bone tumor-targeted nanocatalytic drug T-HCN@CuMS Fig. 9 As shown: (A) Live and dead staining of 143B cells in different treatment groups, (B) using DCFH-DA indicator probe to observe the content of reactive oxygen species in 143B cells in different treatment groups, (C) using JC-1 probe to observe the depolarization of mitochondria in 143B cells in different treatment groups, (D) using Annexin-V-FITC probe to observe the regulation of cells in different treatment groups. Group I: PBS, Group II: PBS+L, Group III: T-HCN@MS, Group IV: T-HCN@MS+L, Group V: T-HCN@CuMS, Group VI: T-HCN@CuMS+L, laser irradiation conditions 808nm, 0.15W cm -2 This indicates that the bone tumor-targeted nanocatalytic drug T-HCN@CuMS can effectively kill bone tumor cells through the combination of near-infrared photocatalysis, chemical catalysis, and copper death. A large amount of reactive oxygen species are produced during the chemical catalysis and near-infrared photocatalysis, inducing apoptotic phenotypes such as mitochondrial depolarization and cell membrane phosphatidylserine externalization in tumor cells.

[0085] The properties of T-HCN@CuMS-induced copper death in tumor cells Fig.10 As shown in the figure, through immunofluorescence (IF) analysis, significant DLAT oligomerization appeared in the 143B cells of the T-HCN@CuMS treatment group, and the expression of ferredoxin (FDX1) and lipoic acid synthase (LIAS) in the 143B cells of the T-HCN@CuMS treatment group was also significantly reduced, indicating that T-HCN@CuMS has excellent properties of inducing copper death of tumor cells.

[0086] Application Example 4

[0087] Establishment of nude mouse orthotopic osteosarcoma model, when the orthotopic tumor size is ~50mm 3 The tumor-bearing nude mice were randomly divided into 6 groups, with 10 mice in each group. They were treated with different treatments: Group I: PBS, Group II: PBS+L, Group III: T-HCN@MS, Group IV: T-HCN@MS+L, Group V: T-HCN@CuMS, Group VI: T-HCN@CuMS+L. The laser irradiation conditions were 808 nm, 0.15 W cm-2 Dosage: 10 mg kg -1 . The changes in body weight and tumor volume of nude mice in different treatment groups were recorded. After the treatment, H&E staining, TUNEL apoptosis staining, immunohistochemical staining of tumor cell proliferation marker Ki67, immunofluorescence staining of copper death markers DLAT, FDX1, and LIAS, and immunofluorescence staining of tumor migration marker ESM1 were performed on the tumor tissues of different treatment groups to observe the tumor metastasis in representative lung tissues of different treatment groups. H&E staining was performed on the main tissues and organs of nude mice in different treatment groups, including heart, liver, spleen, lung, and kidney. Blood routine tests and biochemical indices of liver and kidney function were performed to systematically evaluate the therapeutic effects, anti-metastasis efficacy, and toxic side effects of nanomedicines. The results are as follows Figure 15-19 shown.

[0088] Fig.15 Different treatment groups: (A) solid image of tumor-bearing nude mice after treatment, (B) tumor volume change curve, (C) tumor weight change curve of nude mice. Group I: PBS, Group II: PBS+L, Group III: T-HCN@MS, Group IV: T-HCN@MS+L, Group V: T-HCN@CuMS, Group VI: T-HCN@CuMS+L, laser irradiation conditions: 808 nm, 0.15 W cm -2 Dosage: 10 mg kg -1 .

[0089] Fig.16 (A) Solid images and (B) fluorescence images of representative lung tissues in different treatment groups: Group I: PBS, Group II: PBS+L, Group III: T-HCN@MS, Group IV: T-HCN@MS+L, Group V: T-HCN@CuMS, Group VI: T-HCN@CuMS+L, laser irradiation conditions: 808 nm, 0.15 W cm -2 Dosage: 10 mg kg -1 .

[0090] Fig.17(A) H&E staining, TUNEL apoptosis staining, immunohistochemical staining of Ki67, a tumor cell proliferation marker, immunofluorescence staining of DLAT, FDX1, and LIAS, and immunofluorescence staining of ESM1, a tumor migration marker, for tumor tissues in different treatment groups. (B) Statistical analysis of Ki67, FDX1, LIAS, and ESM1. Group I: PBS, Group II: PBS+L, Group III: T-HCN@MS, Group IV: T-HCN@MS+L, Group V: T-HCN@CuMS, Group VI: T-HCN@CuMS+L. Laser irradiation conditions: 808 nm, 0.15 W cm -2 Dosage: 10 mg kg -1 .

[0091] H&E staining of the main tissues and organs of nude mice in different treatment groups: heart, liver, spleen, lung, and kidney Fig.18 As shown: Group I: PBS, Group II: PBS+L, Group III: T-HCN@MS, Group IV: T-HCN@MS+L, Group V: T-HCN@CuMS, Group VI: T-HCN@CuMS+L, laser irradiation conditions: 808 nm, 0.15 W cm -2 Dosage: 10 mg kg -1 .

[0092] Blood routine and liver and kidney function biochemical indexes of nude mice in different treatment groups were measured as follows Fig.19 As shown: Group I: PBS, Group II: PBS+L, Group III: T-HCN@MS, Group IV: T-HCN@MS+L, Group V: T-HCN@CuMS, Group VI: T-HCN@CuMS+L, laser irradiation conditions: 808 nm, 0.15 W cm -2 Dosage: 10 mg kg -1 .

[0093] Figure 15-19 The results show that the targeted near-infrared photocatalysis-chemical catalysis-copper death combined treatment of nanocatalytic drug T-HCN@CuMS can significantly inhibit the growth of malignant in situ bone tumors and the occurrence of lung metastasis. After 20 days of treatment, obvious tumor cell apoptosis and copper death can be observed in the tumor tissue section staining, and tumor cell proliferation is significantly inhibited. No obvious tissue and organ toxicity and side effects were observed in the staining of major tissue and organ sections, blood routine tests, and liver and kidney function biochemical indexes, further proving that the nanocatalytic drug T-HCN@CuMS has ideal biosafety.

Claims

1. A method for preparing a nanocatalytic drug, characterized in that: The preparation method comprises: (1) After dispersing the metal phase molybdenum disulfide 1T-MoS2 nanosheets, adding copper chloride solution to react to obtain copper coordinated metal phase molybdenum disulfide nanosheets CuMS; (2) After dispersing carbon nitride HCN nanosheets, add CuMS to react and obtain nanocatalytic drug HCN@CuMS; (3) Disperse the nanocatalytic drug HCN@CuMS and add cRGD fk -PEG 2k -DSPE, and obtain the nanocatalytic drug T-HCN@CuMS with bone tumor targeting; In step (2), the preparation method of the HCN nanosheets is: (2-1) calcining urea in an air atmosphere to obtain a bulk carbon nitride material; (2-2) mixing a mixture of sodium chloride and potassium chloride with a bulk carbon nitride material and calcining the mixture in a nitrogen atmosphere to obtain carbon nitride powder; (2-3) adding carbon nitride powder into a nitric acid solution to obtain acidified carbon nitride; (2-4) The acidified carbon nitride was ultrasonically exfoliated in aqueous solution, and HCN nanosheets in the range of 8000-10000 rpm were obtained by step centrifugation.

2. The method for preparing the nanocatalytic drug according to claim 1, characterized in that: In step (1), the preparation method of the 1T-MoS2 nanosheets is as follows: ammonium heptamolybdate tetrahydrate and thiourea are dissolved together and then subjected to a hydrothermal reaction to obtain a metallic phase molybdenum disulfide material 1T-MoS2; 1T-MoS2 is subjected to ultrasonic exfoliation, and 1T-MoS2 nanosheets in the range of 9000-12000 rpm are obtained by step-by-step centrifugation.

3. The method for preparing the nanocatalytic drug according to claim 2, characterized in that: The molar mass ratio of the tetrahydrated ammonium heptamolybdate to thiourea is 1:1-30, the temperature of the hydrothermal reaction is 180-200°C, and the reaction time is 18-24 hours.

4. The method for preparing the nanocatalytic drug according to claim 3, characterized in that: The feeding ratio of the 1T-MoS2 nanosheets to copper chloride is: 1-5 mL of 8 mM copper chloride solution is added for every 10 mg of 1T-MoS2 nanosheets.

5. The method for preparing the nanocatalytic drug according to claim 1, characterized in that: In step (2), the added amount of CuMS is 5-20% of the HCN nanosheets.

6. A nanocatalytic drug obtained according to the preparation method according to any one of claims 1 to 5.

7. Use of the nanocatalytic drug according to claim 6 in the preparation of bone tumor drugs.

Citation Information

Patent Citations

  • Nano catalyst for tumor treatment, and preparation method and application thereof

    CN110974978A

  • Homologous targeting tannic acid copper albumin composite nanoparticle and preparation method and anti-tumor application thereof

    CN113786486A